The Role of Intellectual Capital in Improving Employee Performance through Employee Engagement in the Hybrid Work Era - Budi Hasyim; Aswan; Erick Karunia; Shalahuddin; Muh. Irfandy Azis; Riyans Ardiansyah; Deni Marsha (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This research is motivated by changes in the post-pandemic work system that have encouraged the implementation of hybrid work in the education sector, requiring organizations to optimally manage intellectual capital while maintaining employee engagement to improve performance. This study aims to analyze the effect of intellectual capital on employee performance, with employee engagement as a mediating variable, in the education industry in North Kalimantan. The research method used a quantitative approach with a survey technique of lecturers and education staff at several universities in North Kalimantan. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that intellectual capital has a positive and significant effect on employee performance. Employee engagement has also been shown to have a positive and significant effect on employee performance. In addition, employee engagement significantly mediates the relationship between intellectual capital and employee performance. These findings confirm that intellectual capital development will have a stronger impact on performance when supported by a high level of employee engagement. This study concludes that integrating intellectual capital management strategies and increasing employee engagement are key to improving performance in the hybrid work era in the education sector.